Sleep medicine: Practice, challenges and new frontiers - Parrino, Liborio; Halasz, Peter; Szucs, Anna; Thomas, Robert J.; Azzi, Nicoletta; Rausa, Francesco; Pizzarotti, Silvia; Zilioli, Alessandro; Misirocchi, Francesco; Mutti, Carlotta (Frontiers in Neurology, 2022)
Sleep medicine is an ambitious cross-disciplinary challenge, requiring the mutual integration between complementary specialists in order to build a solid framework. Although knowledge in the sleep field is growing impressively thanks to technical and brain imaging support and through detailed clinic-epidemiologic observations, several topics are still dominated by outdated paradigms. In this review we explore the main novelties and gaps in the field of sleep medicine, assess the commonest sleep disturbances, provide advices for routine clinical practice and offer alternative insights and perspectives on the future of sleep research.